1992
DOI: 10.1172/jci116070
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin-like growth factor-I and its receptor in rat aorta after balloon denudation. Evidence for local bioactivity.

Abstract: Local production of growth factors may play a major role in vascular repair after injury. We examined the regulation of insulin-like growth factor-I (IGF-I) and its specific membrane receptor in balloon-denuded rat aorta. Aortic IGF-I mRNA and radioimmunoassayable IGF-I content increased severalfold after balloon denudation with a peak at 7 d after injury. This coincided with a reciprocal 25% decrease in IGF-I receptor mRNA content and a 40% decrease in total '25I-IGF-I binding.Scatchard analysis indicated a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
57
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 27 publications
5
57
0
1
Order By: Relevance
“…IGFBPs serve as carrier proteins for the IGFs in both vascular and extravascular tissues, can inhibit or potentiate IGF biologic activity in a tissue-specific manner and participate in the local regulation of growth and repair processes (Rechler & Nissley 1990, Clemmons 1991, Drop et al 1991, Shimasaki & Ling 1991. In EC, IGFs and IGFBPs are known to affect several metabolic processes (King et al 1985, Bar et al 1987a, 1988a, are involved in potential interplay between vascular endothelium and subendothelial components (Hansson et al 1987, 1989, Delafontaine et al 1991, Khorsandi et al 1992, Nakao et al 1992, Taylor et al 1993) and may play a role in the intrinsic growth of normal and diseased blood vessels (King et al 1985, Nicosia et al 1994.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGFBPs serve as carrier proteins for the IGFs in both vascular and extravascular tissues, can inhibit or potentiate IGF biologic activity in a tissue-specific manner and participate in the local regulation of growth and repair processes (Rechler & Nissley 1990, Clemmons 1991, Drop et al 1991, Shimasaki & Ling 1991. In EC, IGFs and IGFBPs are known to affect several metabolic processes (King et al 1985, Bar et al 1987a, 1988a, are involved in potential interplay between vascular endothelium and subendothelial components (Hansson et al 1987, 1989, Delafontaine et al 1991, Khorsandi et al 1992, Nakao et al 1992, Taylor et al 1993) and may play a role in the intrinsic growth of normal and diseased blood vessels (King et al 1985, Nicosia et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have described modifications of various IGF system peptides following hypoxic-ischemic brain injury (Klempt et al 1992, Lee et al 1992, Beilharz et al 1993, Lee & Bondy 1993, Stephenson et al 1995, Johnston et al 1996, Sandberg et al 1996, hypoxia induced by reduced uterine blood flow (McLellan et al 1992, Price et al 1992, Owens et al 1994, Asano et al 1995, hypoxia-induced pulmonary hypertension (Perkett et al 1992, Dempsey et al 1994, Townsend & Stenmark 1995, myocardial ischemia (Reiss et al 1994, Buerke et al 1995, Kluge et al 1995 and acute tubular necrosis (Noguchi et al 1993, Tsao et al 1995. In experimental vascular injury, a context in which initial EC proliferation occurs in relative hypoxia, studies have shown induction of aortic IGF-I mRNA in the vascular wall after balloon denudation (Cercek et al 1990, Khorsandi et al 1992 while immunohistochemical studies have described increased IGF-I and IGF-II protein accumulation during repair of injured arterial intima (Hansson et al 1987, 1989, Levinovitz et al 1992. However, little is known about the effect of hypoxia on the IGF system in vascular EC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IGF-1 receptor is highly expressed in the VSMC of intact arteries and in cultured VSMC (7,47).…”
mentioning
confidence: 99%
“…Growth factors, such as platelet-derived growth factor (PDGF) and insulin-like growth factor 1 (IGF-1), and their receptors show increased expression in the arterial wall after balloon angioplasty. [2][3][4][5][6] However, the biological responses elicited by these 2 agonists are different in that PDGF mediates both smooth muscle cell proliferation and migration whereas IGF-1 specifically induces only smooth muscle cell migration. 7 Ligand binding to the PDGF and IGF-1 receptor tyrosine kinases induces autophosphorylation of tyrosines within the cytoplasmic domain of the receptors, resulting in the recruitment and activation of specific signaling molecules that may mediate the migration and proliferation of vascular smooth muscle cells in response to vascular injury.…”
mentioning
confidence: 99%